Effects of Housing Transfer Taxes on Household Mobility - Essi Eerola; Oskari Harjunen; Teemu Lyytikäinen; Tuukka Saarimaa (Center for Economic Studies and ifo Institute (CESifo), 2019)
Housing transfer taxes are fiscally important in many countries despite evidence of substantial welfare losses found in several quasi-experimental studies. Research designs used in this prior literature are prone to attenuation bias due to spillovers from mobility or trading across control and treatment groups. We account for these spillovers by combining quasi-experimental empirical analysis with a one-sided housing market model where households act as both buyers and sellers. Using a Finnish tax reform and total population register data, we find that an increase in the transfer tax has a significant negative effect on household mobility. We calibrate our theoretical model to match the mobility rates in our data and our quasi-experimental estimate. In our setting, relying only on the quasi-experiment and ignoring the spillovers would lead to a 20% underestimation of the effect. We argue that the welfare costs of transfer taxes are larger than previously thought.
Keywords: H21; R21; R23; 330; household mobility; spillover; transfer tax; welfare cost